1990
DOI: 10.1016/0041-008x(90)90086-a
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of anatoxin-A in the conscious rat

Abstract: Cardiovascular Effects of Anatoxin-A in the Conscious Rat. SJREN, A.-L., AND FEUERSTEIN, G. (1990). Toxicol. Appl. Pharmacol. 102,91-100. The effects ofanatoxin-A on mean arterial pressure (MAP), heart rate, cardiac index (CI), and blood flow (BF) in hindquarter (HQ), renal (R). and mesenteric (M) vascular beds were studied after intravenous (iv) and intracerebroventricular (icv) administration in the conscious rat. The pharmacological profile of anatoxin-A was further compared to nicotine administered iv an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 16 publications
2
9
1
Order By: Relevance
“…However, involvement of the cyclooxygenase pathway has not been verified in in vivo rat experiments [25,26]. In parallel to these latter findings, we did not observe any contribution of prostaglandins to CGRPinduced dilation in in vitro rat kidney vasculature, since indomethacin had no effect on the responses.…”
Section: Discussionsupporting
confidence: 74%
“…However, involvement of the cyclooxygenase pathway has not been verified in in vivo rat experiments [25,26]. In parallel to these latter findings, we did not observe any contribution of prostaglandins to CGRPinduced dilation in in vitro rat kidney vasculature, since indomethacin had no effect on the responses.…”
Section: Discussionsupporting
confidence: 74%
“…It is likely the latter was due to a venodilator action of human a-CGRP (Tornebrandt et al, 1987;Crossman et al, 1987; but see Al-Kazwini et al, 1987;Marshall et al, 1988). The present results, therefore, provide some explanation for the conflicting data in the literature regarding the cardiac haemodynamic effects of CGRP (DiPette et al, 1987;Lappe et al, 1987;Siren & Feuerstein, 1988;Ando et al, 1990) (see Introduction), since it is apparent that the effects of the peptide depend on the dose used. Moreover, it may be that the cardiac haemodynamic responses to bolus injections of CGRP would give a less clear picture of the interrelated changes that were seen in the present study, particularly with the infusion of the higher dose of human a-CGRP.…”
Section: Discussioncontrasting
confidence: 34%
“…Using this approach DiPette et al (1987) observed a small increase, while Ando et al (1990) found no change, in cardiac output after administration of rat and human a-CGRP, respectively. In contrast, Siren & Feuerstein (1988) measured cardiac output intermittently with the thermodilution technique in conscious rats and reported an increase of 95 + 16mlmin--kg1' in cardiac index in response to a bolus dose of 1.0 nmol kg-l rat CGRP, but found doses of 0.1 and 10nmol kg-I were without significant effect. However, Lappe et al (1987) recorded I Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%
“…In con scious rats, intracerebroventricularly administered CGRP increased (6) or induced no change (21) in arterial blood pressure. In the present study performed under urethane anesthesia, intracerebroventricularly administered a CGRP induced a marked decrease in arterial blood pres sure.…”
Section: Discussionmentioning
confidence: 99%
“…However, after desensitization of peripheral CGRP receptors by repeated intravenous bolus administration of a-CGRP, intracerebroventricular administration of this peptide did not induce any significant decrease or rather induced an increase in arterial blood pressure. Peripheral ly administered a-CGRP has intense hypotensive and vasodilator actions (6,(21)(22)(23)(24). Furthermore, 8% leakage of a-CGRP from the lateral brain ventricle to the peripheral circulation was demonstrated in rats (25).…”
Section: Discussionmentioning
confidence: 99%